2007
DOI: 10.2214/ajr.05.1484
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Cathartic-Free Colorectal Cancer Screening Test Using Virtual Colonoscopy: A Feasibility Study

Abstract: Image processing tools combining thresholding, expansion, and convolution were the most useful for stool subtraction. Laxative-free colon examinations using barium for stool labeling can be performed at CT colonography with or without stool subtraction with high accuracy. Further study is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…The former of these problems may become less of an issue now that routine use of fluid/faecal tagging has been introduced, and may improve further with software enhancements like electronic subtraction negating the need for onerous bowel preparation [28]. These improvements make prep-less CTC a reality [29]. Another technical advance might be the reported combination of CTC with PET that enables the malignant potential of polyps to be further characterised [30,31], although this combined technique is still in its infancy.…”
Section: Resultsmentioning
confidence: 99%
“…The former of these problems may become less of an issue now that routine use of fluid/faecal tagging has been introduced, and may improve further with software enhancements like electronic subtraction negating the need for onerous bowel preparation [28]. These improvements make prep-less CTC a reality [29]. Another technical advance might be the reported combination of CTC with PET that enables the malignant potential of polyps to be further characterised [30,31], although this combined technique is still in its infancy.…”
Section: Resultsmentioning
confidence: 99%
“…However, several studies have demonstrated that conventional methods that have been developed for fluid-tagging CTC tend to fail in lfCTC, and that new approaches are needed. [8][9][10]20,[36][37][38] Unless suitable visualization and detection tools are developed for lfCTC, the clinical potential of lfCTC might never be realized. Our study represents one of the very first efforts toward developing such interpretation tools.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, attempts to segment tagged regions more precisely with a low CT number threshold can segment parts of pseudoenhanced native soft tissue, including polyps, as tagged region. 9,10 In this study, we hypothesized that the identification of poorly tagged residual materials and partial-volume artifacts could be improved in lfCTC by virtual tagging of such artifacts. We note that the observed radiodensity of tagged materials tends to be diluted by the partial-volume effect ͑PVE͒ that occurs within the material interface between lumen air and nonair materials, and that such diluted tagged materials appear similar to soft tissue ͓Figs.…”
Section: Introductionmentioning
confidence: 99%
“…Results from this study highlight the importance of bowel preparation although, in the future, it may be possible to reliably differentiate fecal material from polyps using fecal tagging [10] , "electronic cleansing" of colonic fluid [16] or contrast-enhanced studies [27] . Other helpful developments may also include new fecal subtraction algorithms [28] , workstation modifications to facilitate polyp detection [29] , improved software and new training prog rams for radiologists [30] .…”
Section: Discussionmentioning
confidence: 99%